Financial market risk and gold investment in an emerging market: the case of Turkey - Bayram, Kamola; Abdullah, Adam; Meera, Ahamed Kameel Mydin (IIUM Press, 2017)
This study aims to identify the opportunity cost of holding gold, in relation to the stock market for case of Turkey. The focus is to detect if gold acts as a safe haven or a hedge asset in times of distress. The Threshold GARCH (TARCH) model was utilized. The analysis used daily data for the period 2005-2014. The data for selling prices of gold was represented by selling prices derived from Precious Metals and Diamonds Markets (PMDM). The returns on Borsa Istanbul (BIS) was employed to represent aggregate prices of stock market investment. It was found that gold has safe haven asset features which shows that gold outperforms the average portfolio during times when stock market faces distress.